A relação de dimensões do perfil dos empreendedores em startups que crescem: uma análise configuracional - Peixoto, Gaspar Antonio (Universidade do Vale do Rio dos Sinos, 2021)
The role played by owners of startups and their relationship with the growth of their businesses attracts the interest of researchers from various disciplines. However, regarding the subject of the ideal entrepreneurial profile, the literature is fragmented. As such, we propose a study to expand knowledge about the relationship between key characteristics of the entrepreneurial profile and startup growth. Using a configurational approach, we analyzed data from 49 startup entrepreneurs to identify combinations of the dimensions that are present in growing startups: individual entrepreneurial orientation, psychological capital, human capital, and social capital. In isolation, none of the dimensions proved mandatory to produce growth in organizations. However, sufficiency analysis showed one successful configuration for each of the above types of capital. The study findings indicate that startups coming from academia are strongly driven by their founders’ high levels of education and low levels of experience. This profile favors the use of technological capabilities to the detriment of managerial capabilities, implying a tendency for the organization to focus more on the development of new products and less on business management. The low experience levels of university entrepreneurs affect their identification of market opportunities and limits the startup’s formation of cooperative networks. Therefore, obtaining support from incubators and accelerators have proven to be a vital strategy for startups to overcome these shortcomings. We also identify heavy influence from the Covid-19 pandemic on entrepreneurial behavior, particularly in the ‘hope and optimism’ dimensions of psychological capital. This research extends the understanding of how different configurations of entrepreneurial characteristics enhance the growth of startups and reinforce the role of incubators and accelerators in compensating for missing characteristics in management teams. From a managerial perspective, the work supports the analysis of entrepreneurial characteristics, both for creators of already-established startups and for individuals intending to become entrepreneurs. The study also helps mentors, incubators, accelerators, and investors to select the best prospects and, ultimately, to focus efforts on the individual characteristics that most enhance the growth of the startups they support.
Keywords: Empreendedorismo; Crescimento de startups; Perfil empreendedor; Orientação empreendedora individual; Capital humano; Capital psicológico; Capital social; Entrepreneurship; Startups growth; Entrepreneurial profile; Individual entrepreneurial orientation; Psychological capital; Human capital; Social capital; ACCNPQ::Ciências Sociais Aplicadas::Administração